2020
DOI: 10.1177/2045894020950187
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic right ventricular function response to incremental exercise in pulmonary hypertension

Abstract: Pulmonary hypertension is a progressive disease whose survival is linked to adequate right ventricle adaptation to its afterload. In the current study, we performed an in-depth characterization of right ventricle function during maximum incremental exercise in patients with pulmonary hypertension and how it relates to exercise capacity. A total of 377 pulmonary hypertension patients who completed a maximum symptom-limited invasive cardiopulmonary exercise testing were evaluated to identify 45 patients with hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
2
10
0
3
Order By: Relevance
“…Maximum VO 2 is an important prognostic indicator in patients with heart failure. 25,26 In the present study, similar to prior reports, HFpEF was associated with reduced submaximum 27 and maximum VO 2 (%predicted). 28,29 Extrapolated maximum VO 2 has been shown to closely correlate with actual maximum VO 2 attained during exercise and is independent of exercise duration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Maximum VO 2 is an important prognostic indicator in patients with heart failure. 25,26 In the present study, similar to prior reports, HFpEF was associated with reduced submaximum 27 and maximum VO 2 (%predicted). 28,29 Extrapolated maximum VO 2 has been shown to closely correlate with actual maximum VO 2 attained during exercise and is independent of exercise duration.…”
Section: Discussionsupporting
confidence: 91%
“…We recently showed that in HFpEF, RV function and its SV deteriorate by 50% of the peak VO 2 . 27 Consequently, the CO is insufficient to meet the increasing Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiologisch konnte dieser Mechanismus bei einem Patienten mit einer durch eine retroperitoneale Fibrosierung hervorgerufenen Obstruktion der Vena cava inferior vor und nach Dilatation bestätigt werden [106]. Aus der gleichen Arbeitsgruppe folgten weitere Untersuchungen: prognostische Relevanz einer belastungsinduzierten PH [73] bei HFpEF-Patienten [107], RV-Funktion unter Belastung [83,108], Unterschiede der peripheren Sauerstoffausschöpfung unter Belastung [109]). Andere Studien dieser Autoren definieren die prognostische Bedeutung einzelner spiroergometrischer Befunde [110] bzw.…”
Section: Zusätzlich Mittels Icpet Erhobene Klinische Befundeunclassified
“…2 slope) mit zentralen Belastungsparametern (maximale Last, Spitzen-Sauerstoffaufnahme, VO 2 peak und der Sauerstoffaufnahme an der anaeroben Schwelle (VO 2 @AT), HZV, PCWP, totaler pulmonaler Widerstand, TPR und V D /VT. Bei 27 Patienten mit interstitieller Lungenkrankheit (ILD) wurde die Hämodynamik unter Belastung im Vergleich zu Kontrollen gegenüber den Nicht-PH Patienten aufwiesen[73,83].Bei 30 CHF-Patienten wurde die Beziehung zwischen VE/VCO 2 slope und der rechtsventrikulären (RV-)Funktion sowie hämodynamischer Variablen in Ruhe und unter Belastung untersucht [84]. VE/VCO 2 slope war dabei positiv korreliert mit dem PVR in Ruhe und unter Belastung sowie dem PCWP in Ruhe, und invers korre-Legende: COPD: Chronisch obstruktive Lungenerkrankung; ILD: interstitielle Lungenerkrankung; IPAH: Idiopathische Pulmonale Arterielle Hypertonie; PAH: Pulmonale Arterielle Hypertonie; HFpEF: Herzinsuffizienz mit erhaltener systolischer Pumpfunktion; CHF: Chronische Herzinsuffizienz; HFrEF: Herzinsuffizienz mit reduzierter systolischer Pumpfunktion; FM: Fickʼsche Methode; TD: Thermodilution; PH: Pulmonale Hypertonie liert mit der RV-…”
unclassified